The Prospect of Electrical Enhanced Oil Recovery for Heavy Oil: A Review - Muhammad Khairul Afdhol; Tomi Erfando; Fiki Hidayat; Muhammad Yudatama Hasibuan; Shania Regina (Universitas Islam Riau (UIR) Press, 2019)
This paper presents a review of electrical heating for the recovery of heavy oil which the work adopts methods used in the past and the prospects for crude oil recovery in the future. Heavy oil is one of the crude oils with API more than 22 which has the potential to overcome the current light oil crisis. However, high viscosity and density are challenges in heavy oil recovery. The method is often used to overcome these challenges by using thermal injection methods, but this method results in economic and environmental issues. The electrical heating method could be a solution to replace conventional thermal methods in which the methodology of electrical heating is to transfer heat into the reservoir due to increasing oil mobility. Because the temperature rises, it could help to reduce oil viscosity, then heavy oil will flow easily. The applications of electrical heating have been adopted in this paper where the prospects of electrical heating are carried out to be useful as guidelines of electrical heating. The challenge of electrical heating is the excessive heat will damage the formation that must be addressed in the prospect of electrical heating which must meet energy efficiency. The use of Artificial intelligence becomes a new technology to overcome problems that are often found in conventional thermal methods where this method could avoid steam breakthrough and excessive heat. Therefore, it becomes more efficient and could reduce costs.